2020
DOI: 10.1038/s41467-020-19527-w
|View full text |Cite
|
Sign up to set email alerts
|

A clinically applicable deep-learning model for detecting intracranial aneurysm in computed tomography angiography images

Abstract: Intracranial aneurysm is a common life-threatening disease. Computed tomography angiography is recommended as the standard diagnosis tool; yet, interpretation can be time-consuming and challenging. We present a specific deep-learning-based model trained on 1,177 digital subtraction angiography verified bone-removal computed tomography angiography cases. The model has good tolerance to image quality and is tested with different manufacturers. Simulated real-world studies are conducted in consecutive internal an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(79 citation statements)
references
References 42 publications
3
76
0
Order By: Relevance
“…The results of this study showed that the postoperative vascular stenosis rate in the DSA group was much lower than that before the surgery, which indicates that stent placement can achieve a good effect in the treatment of vascular restenosis. Such results were in line with the research conclusion of Shi et al [ 19 ]. As the treatment of cardiovascular interventions becomes more and more complex, the success of the operation will depend more on the accuracy of the guidance system, improving the success rate of cardiovascular interventions and clear long-term curative effects.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed that the postoperative vascular stenosis rate in the DSA group was much lower than that before the surgery, which indicates that stent placement can achieve a good effect in the treatment of vascular restenosis. Such results were in line with the research conclusion of Shi et al [ 19 ]. As the treatment of cardiovascular interventions becomes more and more complex, the success of the operation will depend more on the accuracy of the guidance system, improving the success rate of cardiovascular interventions and clear long-term curative effects.…”
Section: Discussionsupporting
confidence: 93%
“…Our BI analyses used site heterogeneous models and the results show their power for resolving phylogenetic relationships with Elateridae and provide for an additional example that model adequacy is critical for accurate tree reconstruction in mitochondrial phylogenomics [ 34 ]. Multiple tree searches and thorough analyses aimed to test the effect of random trapping of the analysis in a local optimum [ 72 ]. In such a way, we produced the phylogeny with a much higher statistical support.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated DLMs for the detection of intracranial aneurysms on CTA [18,[20][21][22] and time-of-flight (TOF)-MRA [23][24][25] and investigated whether deep learning enhancement could increase the diagnostic performance of human readers [20,25]. In the study by Park et al, artificial intelligence assistance increased the detection sensitivity of radiologists and of a neurosurgeon (2-12 years of experience) for UIAs on CTA significantly from 83% to 89% [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have introduced several approaches for deep learning-based detection of aneurysms on CTA [18,[20][21][22] or magnetic resonance angiography (MRA) [23][24][25], compared the accuracy of the DLM to human readers, and investigated the deep learning-augmented diagnostic performance of physicians [20,25]. However, these studies did not include patients with aSAH and focused on unruptured intracranial aneurysms (UIAs) [20,25].…”
Section: Introductionmentioning
confidence: 99%